Pengembangan Center of Honey Kampung Madu Lumbang Kabupaten Probolinggo - Savitri, Emma; Prayitno, Agung; Hadi, Syamsul (Universitas Nusantara PGRI Kediri, 2020)
Lumbang Honey is one of the featured products owned by Lumbang, Probolinggo, East Java. As a featured product, the legality has been issued by the Probolinggo District Government through Probolinggo Regent Decree number 030/1134/426.12/2013. Lumbang honey is supported by 10 Forest Farmer Groups with honey production of 6,206 kg per month in 2014. Although the amount of honey production is very abundant, Lumbang honey has not been able to compete with commercial honey products on the market. This is because the quality and price of Lumbang honey is very diverse. Therefore, The Center of Honey